Kewenangan Penegakan Hukum Pidana Perikanan di Indonesia [Authority of Fisheries Criminal Law Enforcement in Indonesia] - Zahratul'ain Taufik; Atika Zahra Nirmala (UKInstitute, 2026)
Fisheries criminal law enforcement is a vital instrument in maintaining the sustainability of national marine and fisheries resources, particularly in combating IUU Fishing. However, the construction of fisheries criminal law enforcement authority in Indonesia still faces overlapping authority among law enforcement agencies, which impacts coordination effectiveness and legal certainty in the investigation process of fisheries crimes. This study aims to analyze the construction of fisheries criminal law enforcement authority in Indonesia and examine the ideal arrangement of authority within the fisheries law enforcement system. This study is a normative legal research employing statutory and conceptual approaches. The results indicate that the construction of fisheries criminal law enforcement authority is formed by granting authority to multiple law enforcement institutions, namely Fisheries Civil Servant Investigators (PPNS Perikanan), the Indonesian National Police, and the Indonesian Navy. Nonetheless, this multi-institutional authority structure still leads to a disharmony of authority, weak inter-agency coordination, and unclear division of operational competence in law enforcement practices. Therefore, a restructuring of the authority framework is required through regulatory harmonization, clearer division of authority, and the strengthening of coordination mechanisms among law enforcement agencies to create an effective, integrated fisheries law enforcement system that provides legal certainty in combating IUU Fishing. Abstrak. Penegakan hukum pidana perikanan merupakan instrumen penting dalam menjaga keberlanjutan sumber daya kelautan dan perikanan nasional, khususnya dalam pemberantasan IUU Fishing. Namun demikian, konstruksi kewenangan penegakan hukum pidana perikanan di Indonesia masih menghadapi persoalan overlapping authority antarlembaga penegak hukum yang berdampak pada efektivitas koordinasi dan kepastian hukum dalam proses penyidikan tindak pidana perikanan. Penelitian ini bertujuan untuk menganalisis konstruksi kewenangan penegakan hukum pidana perikanan di Indonesia serta mengkaji bentuk penataan kewenangan yang ideal dalam sistem penegakan hukum perikanan. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa konstruksi kewenangan penegakan hukum pidana perikanan dibentuk melalui pemberian kewenangan kepada beberapa institusi penegak hukum, yaitu PPNS Perikanan, Kepolisian Negara Republik Indonesia, dan TNI Angkatan Laut. Namun demikian, pengaturan kewenangan yang bersifat multi-institusional tersebut masih menimbulkan disharmonisasi kewenangan, lemahnya koordinasi antarlembaga, dan belum jelasnya pembagian kompetensi operasional dalam praktik penegakan hukum. Oleh karena itu, diperlukan penataan ulang konstruksi kewenangan melalui harmonisasi regulasi, penegasan pembagian kewenangan, dan penguatan mekanisme koordinasi antarlembaga penegak hukum guna menciptakan sistem penegakan hukum perikanan yang efektif, terpadu, dan memberikan kepastian hukum dalam pemberantasan IUU Fishing.